BLURRED LINES: HOW GENERATION Z IN INDONESIA PERCEIVES ISLAMIC AND CONVENTIONAL BANKING AS IDENTICAL SYSTEMS - Hamdi, Muhammad; Fachrudin, Kurniawan Ali (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This study investigates systematic misconceptions among Generation Z based on gender. Using a mixed-methods approach, data were collected from 303 Generation Z participants in Yogyakarta, Indonesia. Data were collected through focus group discussions and structured surveys, which were analyzed using exploratory factor analysis (EFA) and reliability testing. The results indicate that the dominant factor exposed from this misconception is perceived banking convergence. Furthermore, the level of understanding among males shows higher values compared to females, particularly for the indicators of shariah home financing, shariah deposits, business loans, banking objectives, and fund management, which have the largest value gaps. Islamic banking institutions need to design more gender-segmented education and communication strategies, with a special emphasis on clarifying the differences in principles and product mechanisms. In addition, institutions need to develop more practical financial literacy campaigns to enhance Generation Z's substantive understanding of the value of Islamic banking.